Caveolin gene expression predicts clinical outcomes for early-stage HER2-negative breast cancer treated with paclitaxel-based chemotherapy in the GeparSepto trial - Williams, Terence M.; Schneeweiss, Andreas; Jackisch, Christian; Shen, Changxian; Weber, Karsten Ernst; Fasching, Peter Andreas; Denkert, Carsten; Furlanetto, Jenny; Heinmöller, Ernst; Schmatloch, Sabine; Karn, Thomas; Szeto, Christopher W.; et al. (Clinical cancer research, 2023)
Caveolin-1 and -2 (CAV1/2) dysregulation are implicated in driving cancer progression and may predict response to nab-paclitaxel. We explored the prognostic and predictive potential of CAV1/2 expression for patients with early-stage HER2-negative breast cancer receiving neoadjuvant paclitaxel-based chemotherapy regimens, followed by epirubicin and cyclophosphamide.We correlated tumor CAV1/2 RNA expression with pathologic complete response (pCR), disease-free survival (DFS), and overall survival (OS) in the GeparSepto trial, which randomized patients to neoadjuvant paclitaxel- versus nab-paclitaxel-based chemotherapy.RNA sequencing data were available for 279 patients, of which 74 (26.5%) were hormone receptor (HR)-negative, thus triple-negative breast cancer (TNBC). Patients treated with nab-paclitaxel with high CAV1/2 had higher probability of obtaining a pCR [CAV1 OR, 4.92; 95% confidence interval (CI), 1.70-14.22; P = 0.003; CAV2 OR, 5.39; 95% CI, 1.76-16.47; P = 0.003] as compared with patients with high CAV1/2 treated with solvent-based paclitaxel (CAV1 OR, 0.33; 95% CI, 0.11-0.95; P = 0.040; CAV2 OR, 0.37; 95% CI, 0.12-1.13; P = 0.082). High CAV1 expression was significantly associated with worse DFS and OS in paclitaxel-treated patients (DFS HR, 2.29; 95% CI, 1.08-4.87; P = 0.030; OS HR, 4.97; 95% CI, 1.73-14.31; P = 0.003). High CAV2 was associated with worse DFS and OS in all patients (DFS HR, 2.12; 95% CI, 1.23-3.63; P = 0.006; OS HR, 2.51; 95% CI, 1.22-5.17; P = 0.013), in paclitaxel-treated patients (DFS HR, 2.47; 95% CI, 1.12-5.43; P = 0.025; OS HR, 4.24; 95% CI, 1.48-12.09; P = 0.007) and in patients with TNBC (DFS HR, 4.68; 95% CI, 1.48-14.85; P = 0.009; OS HR, 10.43; 95% CI, 1.22-89.28; P = 0.032).Our findings indicate high CAV1/2 expression is associated with worse DFS and OS in paclitaxel-treated patients. Conversely, in nab-paclitaxel-treated patients, high CAV1/2 expression is associated with increased pCR and no significant detriment to DFS or OS compared with low CAV1/2 expression.
Gesehen am 20.11.2023